Cancer-Derived Exosomes as Effectors of Key Inflammation-Related Players - Othman, Norahayu; Jamal, Rahman; Abu, Nadiah (Frontiers in Immunology, 2019)
Exosomes, a category of small lipid bilayer extracellular vesicles that are naturally secreted by many cells (both healthy and diseased), carry cargo made up of proteins, lipids, DNAs and RNAs; all of which are functional when transferred to their recipient cells. Numerous studies have demonstrated the powerful role that exosomes play in the mediation of cell-to-cell communication to induce a pro-tumoral environment to encourage tumour progression and survival. Recently, considerable interest has developed in regards to the role that exosomes play in immunity; with studies demonstrating the ability of exosomes to either metabolically alter immune players such as dendritic cells, T cells, macrophages and natural killer cells. In this review, we summarize the recent literature on the function of exosomes in regulating a key process that has long been associated with the progression of cancer – inflammation and immunity.